Diversity in archaeology : proceedings of the Cambridge Annual Student Archaeology Conference 2020/2021 - Doğan, Elifgül, (Access archaeology., 2022)
Thirty papers explore a wide range of topics such as women's voices in archaeological discourse; researching race and ethnicity across time; use of diversified science methods in archaeology; critical ethnographic studies; diversity in the archaeology of death, heritage studies, and archaeology of 'scapes'.